Changing landscapes in Caribbean education: Are our teachers being adequately prepared for this? [PowerPoint presentation] - Jennings, Zellynne; Anderson, Susan (My University, 2013)
Didacus Jules contends that we need to adopt a radical approach in rethinking education in the Caribbean to make learning fun, more closely related to the digital world, and more relevant to the social issues that beset schools today. This challenge was reiterated by Jessop (2012) who highlighted critical points on transforming education made at the 18th Conference of Commonwealth Education Ministers in Mauritius. Jessop noted that the current decline in Caribbean Examinations Council (CXC) exam results is a signal that young people are leaving school unprepared for the job market-a trend that will have adverse effects on Caribbean economies. Among the suggestions for the way forward is the need to reassess teaching methods so they become more technology-driven and relevant to national development. This paper presents research that critically examines the effectiveness of the different models of teacher education used at The University of the West Indies over a 10-year period (1997-2007), drawing on the experiences of the graduates of the programme, current students, and other stakeholders. The findings point to crucial changes that need to be made if teachers are to be appropriately prepared for the challenges of today's classrooms
Paper presented at the Biennial Conference of The University of the West Indies Schools of Education, 23-25 April, 2013, St. Augustine, Trinidad and Tobago
Keywords: Teacher education; Programme design; Educational models; Educational environment; Programme evaluation; The University of the West Indies, Mona; Conference papers; Jamaica